Answer:
![V_(rms_f)=\sqrt{(3PV)/(2nM)} = \sqrt{(1)/(2)} \sqrt{(3PV)/(M)} = (1)/(√(2)) \sqrt{(3PV)/(M)} = (1)/(√(2)) V_(rms_i)](https://img.qammunity.org/2021/formulas/physics/college/kn2t4v0ngyz6inxhzc5t68l5udmdeftp4v.png)
So then the final answer on this case would be:
![(V_(rms_i))/(√(2))](https://img.qammunity.org/2021/formulas/physics/college/4hbgj0gshm4do0bszxx64j5nblm4bikimk.png)
Step-by-step explanation:
From the kinetic theory model of gases we know that the velocity rms (speed of gas molecules) is given by:
(1)
Where V represent the velocity
R the constant for ideal gases
T the temperature
M the molecular weight of the gas
We also know from the ideal gas law that
![PV= nRT](https://img.qammunity.org/2021/formulas/physics/college/w218506ggrohg2w137pm29c8o0327p0ech.png)
If we solve for T we got:
![T = (PV)/(nR)](https://img.qammunity.org/2021/formulas/physics/college/n4jk3qo8we3zhic0z3n4xqqyoj2j5zi0nj.png)
For the initial state we can replace T into the equation (1) and we got:
![V_(rms_i)= \sqrt{(3R ((PV)/(nR)))/(M)} = \sqrt{(3PV)/(M)}](https://img.qammunity.org/2021/formulas/physics/college/t1qkgifjeb4749x91nvhpcdqx94g4pymi8.png)
For the final state we know that :
And the pressure not change , so then the final velocity would be:
![V_(rms_f)= \sqrt{(3R ((P(V/2))/(nR)))/(M)} = \sqrt{(3P(V/2))/(M)}](https://img.qammunity.org/2021/formulas/physics/college/mhlt9o9epc5qozqjg419bfezcdqj7kq5cg.png)
![V_(rms_f)=\sqrt{(3PV)/(2nM)} = \sqrt{(1)/(2)} \sqrt{(3PV)/(M)} = (1)/(√(2)) \sqrt{(3PV)/(M)} = (1)/(√(2)) V_(rms_i)](https://img.qammunity.org/2021/formulas/physics/college/kn2t4v0ngyz6inxhzc5t68l5udmdeftp4v.png)
So then the final answer on this case would be:
![(V_(rms_i))/(√(2))](https://img.qammunity.org/2021/formulas/physics/college/4hbgj0gshm4do0bszxx64j5nblm4bikimk.png)